The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/ajoc.201700609
|View full text |Cite
|
Sign up to set email alerts
|

Thia‐Michael Addition: An Emerging Strategy in Organic Synthesis

Abstract: The thia-Michael addition reactionh as been demonstrated to be ah ighly powerful tool in organic synthesis. Indeed, the influential natureo ft his reactionh as been wellestablished in the fields of medicinal chemistry,c atalysis, drug discovery,a nd materials science. The emergence of numerous synthetic strategies that take advantage of thia-Michael addition reactions of electron-deficienta lkenes has unleashed countless opportunities for the design and synthesis of diverse biologically relevant organosulfurc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
60
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 112 publications
0
60
0
Order By: Relevance
“…Furthermore, thia-Michael additions of alkyl thiols to electron-poor olefins have been widely studied and applied in organic synthesis. [26] On the other hand, the seleno-Michael reaction of functionalised alkyl selenols has never been described, despite it would represent a powerful tool for the formation of new CÀ Se bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, thia-Michael additions of alkyl thiols to electron-poor olefins have been widely studied and applied in organic synthesis. [26] On the other hand, the seleno-Michael reaction of functionalised alkyl selenols has never been described, despite it would represent a powerful tool for the formation of new CÀ Se bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Themild conditions of conjugate addition, as the Michael reaction has come to be colloquially known, also lend this reaction well to other areas of research such as bioconjugation or dynamic combinatorial chemistry. [4] As aresult, methods to synthesize a,b-unsaturated systems are highly prized. Convenient and efficient pathways include carbonyl olefination [5] and olefin cross-metathesis, [6] although the ability to directly generate a,b-unsaturated carbonyl compounds from their corresponding saturated counterparts by dehydrogenation adds considerable flexibility to synthetic planning.…”
mentioning
confidence: 99%
“…On the basis of above control experiments (Scheme 3), we further initiated our effort to establish the importance of synergistic interaction between Larginine and ionic liquid by using NMR ( 1 H and 13 13 C NMR spectra of a mixture of L-arginine-[bmim]Br was also recorded and it was observed that the carboxylic group of L-arginine in the presence of [bmim]Br showed an upfield shift from 183.090 ppm to 181.066 ppm when compared with 13 C NMR spectra of individual L-arginine. It is worth pointing out that our observations based upon NMR spectra analysis were concordant with the observation of Ren et al [31] where they proposed that the head group of the amino acid along with the guanidine moiety of L-arginine interacts with the ionic liquid.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the fact that there are some useful protocols for the synthesis of b-aryl-b-sulfanyl esters, the requirements of pre-synthesized b-aryl-a,b-unsaturated esters, metal catalyst, strongly basic conditions, longer reaction time and limited substrate scopes (Scheme 1) are some of the major drawbacks of reported methods. [12][13][14] To date, to the best of our knowledge a fully-fledged thia-Michael addition reaction on in situ generated b-aryl-a,b-unsaturated esters…”
Section: Introductionmentioning
confidence: 99%